2020
DOI: 10.1093/intqhc/mzaa099
|View full text |Cite
|
Sign up to set email alerts
|

Human factors/ergonomics work system analysis of patient work: state of the science and future directions

Abstract: Purpose To demonstrate the use and value of the Human Factors/Ergonomics-based Systems Engineering Initiative for Patient Safety (SEIPS) family of work system models for studying and improving patient work. Data Sources : We conducted a review of the published empirical literature applying the SEIPS family of work system models for patient work. Study Selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…This study demonstrated that even without investments in mobile communication technology or building redesigns, self-rooming is acceptable to patients and staff. In line with human factors engineering models of work systems design, [8][9][10][11] this finding suggests that our redesigned workflow is well aligned with the user needs of patient and staff, with task and organizational features adequately balancing out the absences of dedicated technology and building infrastructure. Most patients selected self-rooming as their preferred rooming process and few felt it was less patient friendly than escorted rooming.…”
Section: Discussionsupporting
confidence: 59%
“…This study demonstrated that even without investments in mobile communication technology or building redesigns, self-rooming is acceptable to patients and staff. In line with human factors engineering models of work systems design, [8][9][10][11] this finding suggests that our redesigned workflow is well aligned with the user needs of patient and staff, with task and organizational features adequately balancing out the absences of dedicated technology and building infrastructure. Most patients selected self-rooming as their preferred rooming process and few felt it was less patient friendly than escorted rooming.…”
Section: Discussionsupporting
confidence: 59%
“…Various versions of the SEIPS model have been used by academics and practitioners, but a recent review argued that broader use and benefits can be achieved through 'an easy-to-use version of the model and simplified tools for model application'. 6 This concords with repeated requests we have received for simple, practical tools to apply SEIPS and with the general critique regarding the dearth of easy to use systems engineering tools. 7 Accordingly, we offer SEIPS 101, a simplified, practice-oriented SEIPS model meant for easy use by practitioners, researchers and others, regardless of prior familiarity with SEIPS.…”
mentioning
confidence: 97%
“…There is increasing attention within human factors models on understanding and supporting patients as active participants in their health and care. [28][29][30] Additional work is needed to improve home BP data entry tools to support patient independence in this process; in particular, more development is needed to provide patients with cues and feedback to confirm that they have successfully completed the task. Additionally, trying to better incorporate these data in clinical decision making honors the patient effort required to collect and share these data.…”
Section: Discussionmentioning
confidence: 99%